The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004670000451
|View full text |Cite
|
Sign up to set email alerts
|

Acute poststreptococcal glomerulonephritis following circumcision

Abstract: A case of acute poststreptococcal glomerulonephritis following circumcision is presented. An 11-year-old boy was subjected to ritual circumcision, which was complicated by the infection of the wound and development of oliguria, edema, hematuria and hypertensive encephalopathy 2 weeks later. The diagnosis of poststreptococcal glomerulonephritis was established upon the isolation of Streptococcus pyogenes, increased antistreptolysin O (ASTO) and antiDNAse B titers and hypocomplementemia. The clinical course was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
0
5
0
1
Order By: Relevance
“…Many complications have been cited in different reports [26,27,28,29,30,31]. Surgical risks associated with circumcision, particularly bleeding, penile injury, and local infection, as well as the consequences of the pain experienced with neonatal circumcision, are valid concerns that require appropriate responses [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Many complications have been cited in different reports [26,27,28,29,30,31]. Surgical risks associated with circumcision, particularly bleeding, penile injury, and local infection, as well as the consequences of the pain experienced with neonatal circumcision, are valid concerns that require appropriate responses [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…He was treated with prednisolone for 4weeks. 10 Murugama et al reported a 4-year-old boy from Japan. The patient presented with gross hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Meatal stenosis and rare complications such as poststreptococcal glomerulonephritis have been reported. 35 The treatment with bioenergy is popular, particularly for children suffering from nocturnal enuresis, epilepsy, cerebral palsy, and malignant diseases; treatment with herbs or tea is popular for influenza, diarrhea, and kidney stones. Many nonprofessionals declare themselves as nutritionists and prescribe various diets for children such as glutenand lactose-free or vegetarian.…”
Section: Alternative Medicinementioning
confidence: 99%